THE GENETIC DIVERSITY OF KEJOBONG GOAT BASED ON CYTOCHROME B GENE - J. Jiyanto; S. Sutopo; E. Kurnianto (Diponegoro University, 2014)
The purpose of this research was to identify Kejobong goat based on Cytochrome b gene variationby Polymerase Chain Reaction (PCR)-Sequencing technique and to analyze the genetic relationship byusing phylogenetic tree. Materials used were blood sample of 12 heads of Kejobong goat fromKaligondang, Pengadegan, Kejobong, and Bukateja Districts. The steps of this research included DNAextraction, PCR, electrophoresis and DNA sequencing. Forward primer 5'-tggaatctaaccatgaccaatg-3 'andreverse 3'-ggctattctccttttctggttt-5' were used in PCR process. The results of sequences were thenanalyzed by ClustalW in the MEGA 5. The result of this study showed that DNA could be extractedwell. The good results obtained from sequenced for about 779 bp at the nucleotide of 238 to 1016 inCytochrome b. A total of 7 codons diverse sites were detected (sites of 103; 122; 165; 167; 198; 215 and284) at Kejobong goats. There was change in amino acid at 2 sites, those were at 165 sites (*) replacedby (W) in K1 and K2 samples, and at 215 sites (T) replaced by (A) in all samples of Kejobong goats.Kejobong goats at 4 Districts had low genetic distance (0.000-0.001). The analysis of Cytochrome bgene of Kejobong goats originated from different area showed the high similarity and a close geneticrelationship.